The Effectiveness of Nahdlatul Ulama (NU) Coin Fund Management in Enhancing the Welfare of Pekalongan City's Residents - Zahwa, Qotrunnada Sevia (Al-Muamalat: Jurnal Ekonomi Syariah, 2023)
This study aims to evaluate the effectiveness of Nahdlatul Ulama (NU) Coin fund management in improving community welfare in Pekalongan City, Indonesia. LAZISNU, as one of the Amil Zakat Institutions, has a work program that focuses on collecting infak and alms from the community through the NU Coin movement (NU-care). NU Care-LAZISNU is a non-profit organization under the Nahdlatul Ulama (NU) association. This research is a type of qualitative research with a case study approach using primary data sources and secondary data. This research revealed that the management of NU coin funds in Pekalongan City has not reached the expected level of effectiveness, because only a few branches are consistently involved in fundraising activities, resulting in the planned work program has not reached its maximum potential.Penelitian ini bertujuan untuk mengevaluasi efektivitas pengelolaan dana Koin Nahdlatul Ulama (NU) dalam meningkatkan kesejahteraan masyarakat di Kota Pekalongan, Indonesia. LAZISNU, sebagai salah satu Lembaga Amil Zakat, memiliki program kerja yang berfokus pada pengumpulan infak dan sedekah dari masyarakat melalui gerakan NU Coin (NU-care). NU Care-LAZISNU adalah organisasi nirlaba di bawah asosiasi Nahdlatul Ulama (NU). Penelitian ini merupakan jenis penelitian kualitatif dengan pendekatan studi kasus menggunakan sumber data primer dan data sekunder. Penelitian ini mengungkapkan bahwa pengelolaan dana koin NU di Kota Pekalongan belum mencapai tingkat efektivitas yang diharapkan, karena hanya beberapa cabang yang secara konsisten terlibat dalam kegiatan penggalangan dana, sehingga program kerja yang direncanakan belum mencapai potensi maksimalnya.